UNIVERSITY STUDENTS’ CRITICAL THINKING ABILITY IN LISTENING SKILL - Elsa Ernawati Nainggolan; Hanifah (Getsempena English Education Journal, 2020)
The present study analysed university students’ critical thinking ability on their listening skills. With this purpose in mind, 25 students taking listening subject participated in the study were chosen as the sample of this study. To gather the data, the essay test of critical thinking skill developed by Facione were administered to the participants after they had listened to related audio of conversation and/or monologue. The obtained data were then analysed using holistic critical thinking scoring rubric. The results showed that the core critical thinking skill of interpretation possessed by the students is 61% categorized as low, analysis skill is 65% classified as medium, inference skill holds 68% ranked as medium, evaluation skill gets 56% categorized as low, explanation skill is 54% classified as low, and self-regulation is 68% classified as medium. To add, the total average of students skill related to critical thinking is 62% and is categorized as low. Considering that students in higher education is faced with complex problem and decision making, education practitioner are called to develop critical thinking in language teaching particularly listening skill. Thus, the development of critical thinking in listening would contribute to successful communication.